Generation and gene expression profiling of 48 transcription-factor-inducible mouse embryonic stem cell lines - Yamamizu, Kohei; Sharov, Alexei A.; Piao, Yulan; Amano, Misa; Yu, Hong; Nishiyama, Akira; Dudekula, Dawood B.; Schlessinger, David; Ko, Minoru S. H. (Scientific reports, 2016)
Mouse embryonic stem cells (ESCs) can differentiate into a wide range – and possibly all cell types in vitro , and thus provide an ideal platform to study systematically the action of transcription factors (TFs) in cell differentiation. Previously, we have generated and analyzed 137 TF-inducible mouse ESC lines. As an extension of this “NIA Mouse ESC Bank,” we generated and characterized 48 additional mouse ESC lines, in which single TFs in each line could be induced in a doxycycline-controllable manner. Together, with the previous ESC lines, the bank now comprises 185 TF-manipulable ESC lines (>10% of all mouse TFs). Global gene expression (transcriptome) profiling revealed that the induction of individual TFs in mouse ESCs for 48 hours shifts their transcriptomes toward specific differentiation fates (e.g., neural lineages by Myt1 Isl1 , and St18 ; mesodermal lineages by Pitx1 , Pitx2 , Barhl2 , and Lmx1 a; white blood cells by Myb , Etv2 , and Tbx6 , and ovary by Pitx1 , Pitx2 , and Dmrtc2 ). These data also provide and lists of inferred target genes of each TF and possible functions of these TFs. The results demonstrate the utility of mouse ESC lines and their transcriptome data for understanding the mechanism of cell differentiation and the function of TFs.